International efforts in geriatric radiation oncology. Issue 3 (April 2022) - Naseer, Amara; Cree, Anthea; Simcock, Richard; Jeppesen, Stefan Starup; Morris, Lucinda; Kenis, Cindy; Hashmi, Amira; Dale, William; O'Donovan, Anita
Abstract: Introduction: Geriatric assessment (GA) has been recommended to form part of treatment decision making for older adults with cancer. However despite consensus guidelines from various organizations, GA does not appear to be a part of routine practice in radiation oncology. The aim of the current study was to explore the implementation of GA in radiation oncology. Materials and Methods: This anonymous international survey investigated current use of GA in patients presenting for radiation therapy aged 65 years and over, in accordance with Checklist for Reporting Results of Internet E -Surveys (CHERRIES) guidelines. The survey was designed, using Qualitrics™, an online survey tool. It was distributed via SIOG, social media and radiation oncology professional organizations. Survey responses were analyzed using simple descriptive statistics. An additional analysis by creating a dichotomous variable based on awareness of major clinical practice guidelines and current use of GA. Results: Among 158 respondents, there was relatively low awareness of GA guidelines and low uptake of validated tools and processes. A minority of participants, only 16%, stated that they had a specialized geriatric oncology program in their institution. Approximately a third (34%) of respondents were unaware of any GA clinical practice guidelines. With regard to what way participants assess older patients differently to younger patients, 16% reported formally using specific validated tools, whereas 73% reported an informal assessment based on their own judgment, with 5% reporting no difference between younger and older patients. Regarding the use of validated screening tools for geriatric impairments, over half reported using none (57%). Regarding GA implementation, the main barriers highlighted included a lack of clinical/support staff, a lack of training, knowledge, understanding or experience about GA and a lack of time. Discussion: Relatively low awareness of guidelines and low uptake of formal GA tools and processes were found. The integration of GA principles into radiation oncology appears to be ad hoc and very much in its infancy. There is a clear need for increased interdisciplinary education and collaboration between the disciplines of radiation oncology and geriatric medicine.